Quantification, characteristics, and distribution of microplastics released from waste burning furnaces and their associated health impacts - Sofi Azilan, Aini; Achmad, Syafiuddin; Ahmad Kueh, Beng Hong (Wiley Periodicals, LLC., 2023)
Although investigation of microplastics (MPs) present in air environment has been intensively carried out, quantification, characteristics, and distribution ofMPs released from the waste burning furnace (WBF) has been missing in literature. The aim of this study was to characterize the presence of MPs released from WBFs and analyze their associated health impacts. The examined locations were at two WBFs (nominated as TPS1 and TPS2) in Sidoarjo, Indonesia. MPs were collected using a 9 cm diameter glass beaker for a period of 8 h at two different sampling points, which are 3 and 15 m from each WBF. Several characteristics of MPs in terms of the number of particles, size, shape, color, and polymer type were comprehensively characterized. This study found that the obtained MPs were of fiber type and in the range of 46–77 and 41–59 particles at TPS1 and TPS2, respectively. In general, the polymer types of MPs were, respectively, cellophane and polytetrafluoroethylene at TPS1 and TPS2. Moreover, it was estimated that about 1.9–2.3 MPs can enter the human body via inhalation. This study offers a pilot examination ofMPs released fromWBF and findings from this study are crucial to provide new knowledge as a basis to carefully regulate the use of WBF particularly that are located closely to local community.